Online News Media (Detak Media): Analysis of the Strategic Role in Disseminating Information to the Public in the Context of the Digital Era - Alfarizi; Piriani; Mahdi, Sayed; Suryaningsih (PT FORMOSA CENDEKIA GLOBAL, 2024)
A news media that provides information to the public through an easily accessible online platform. People don't need to buy newspapers to get information, they just need to scroll to get the information. This condition really requires increased gatekeeping or filtering of information from online news media. So that the information conveyed can be factual and can be accounted for. The aim of community service is to provide factual information to the community. Through a good interview, writing and screening process before being given to the public.